Rooted : life at the crossroads of science, nature, and spirit - Haupt, Lyanda Lynn (Little, Brown Spark, 2021)
"In Rooted, cutting-edge science supports a truth that poets, artists, mystics, and earth-based cultures across the world have proclaimed over millennia: life on this planet is radically interconnected. Our bodies, thoughts, minds, and spirits are affected by the whole of nature, and they affect this whole in return. In this time of crisis, how can we best live upon our imperiled, beloved earth?" -- Amazon.com